Induction of genetic variability in kacholam(Kaempferia Galanga L.) - Kanakamany M T (Department of Plant Breeding and Genetics, College of Horticulture, 1997)
The present study "Induction of genetic variability in kacholam, Kaempferia galanga L." was undertaken in the Department of Plant Breeding and Genetics, College of Horticulture, Vellanikkara, during 1992-95. Rhizomes of Kaempferia galanga cv. Vellanikkara local were treated with eight doses of gamma rays (2.5,5.0,7.5, 10.0, 12.5, 15.0, 17.5 and 20.0 Gy) and six concentrations of EMS (0.25,0.50,0.75, 1.0, 1.25 and 1.50%) and MV1, MV2 and MV3 generations were evaluated. LD50 of gamma rays was 20.0 Gy and that of EMS 1.5 per cent. The highest values for yield and yield attributing characters were obtained for 7.5 Gy gamma rays and 0.75 per cent EMS. Gamma rays at 15.0 Gy and EMS at one per cent were most effective in inducing variability for rhizome yield and yield attributes. High estimates of heritability (broad sense) coupled with high genetic advance was observed for number of leaves and rhizome number and direct selection for improvement of these traits will be effective. Correlation coefficient between yield and its components indicated significant positive association of yield with number of leaves, tillers, leaf length, plant spread and rhizome number in the untreated control. Mutagenic treatments induced alterations in the association between rhizome yield and components.